The mark and the act of impregnating - Almozara, Paula Cristina Somenzari (PORTO ARTE: Revista de Artes Visuais, 2018)
This article looks into poetic construction from the idea of “mark” as an act of impregnation. It presents reports on graphic processes resulting from artist residencies in which poetic and documentary actions were developed that relate the mark as a form of impregnation for approximations with the landscape in unknown territories.